An independent center for the origin of bread wheat in the Neolithic period of Georgia in the South Caucasus - Nana Rusishvili; Mindia Jalabadze; Marine Mosulishvili; Stephen Batiuk; David Maghradze; Elisabetta Boaretto; Inga Martkoplishvili; Nana Meladze; David Lordkipanidze (Proceedings of the National Academy of Sciences, 2026)
Bread wheat ( Triticum aestivum L.) is the most popular wheat species in the world today. However, studies on the domestication of wheat have rarely focused on the evolution of this specific species of Triticum . The discussions that have emerged have focused on the evolution of bread wheat, revealing it to have emerged from the hybridization of an already domesticated free-threshing wheat and the wild goatgrass known as Aegilops tauschii Coss. These studies, however, have focused on the previous genetic evidence, with data suggesting a date of circa 7,000 to 6,500 BC, and given the distribution of the parent grains, a locus of the South Caucasus and Southwest Caspian regions for its emergence. This paper discusses the archaeological data, including archaeobotanical and chronometric data from the excavations at Gadachrili Gora and Shulaveris Gora, Georgia of the South Caucasus, which provides physical evidence for the emergence of bread wheat and A. tauschii , supporting the aforementioned studies.